ROLE OF HAMSTRING MUSCLES IN KNEE JOINT STABILITY PROVIDING AND INJURY PREVENTION - Pontaga, Inese (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The aim of our investigation was to determine the ratio of maximal torque values and the torques in the certain positions of range of movements (ROM) between hamstring (H) and quadriceps femoris (Q) muscles at medium and high velocity of movement in concentric (CC) and eccentric (ECC) action of hamstring muscles. The knee muscles of 15 amateur female short and middle distance runners were tested by the dynamometer system in the isokinetic movements with the angular velocity of 90º/s and 240º/s in CC and at the velocity of 90º/s in ECC H/ CC Q muscles contractions. The torque values produced by the muscles are detected at the different angular positions of the ROM with the step of 10º. The ratios of H/ Q muscles torques are calculated. The H/Q muscles maximal torques ratio is 0.51 ± 0.13 at the velocity of 90º/s in CC and 0.60 ± 0.09 in ECC H/ CC Q muscles contractions, and 0.59 ± 0.09 CC at the velocity of 240º/s. The H/Q maximal torques ratio and this ratio in the knee extreme extension and flexion at the ECC contraction of H is higher due to greater torques produced by the H in comparison with Q muscle. The H must be stronger to decelerate the thigh and lower leg extension in the late swing phase of running and to extend the hip in early stance phase to provide powerful sprint running and prevent the knee and H injury. The H/Q muscles torques ratio in extended knee positions are similar in medium (90º/s) and fast (240º/s) velocity of motions because CC action of H muscles cannot prevent extreme knee extension.